Biosecurity Strategies in Poultry Farms and their Impact on Health and Production: A Review - Mohamed , Mohammed hasib; Jasim , Ruya. F. (American Journal of Biology and Natural Sciences, 2025)
His context: While poultry production is a fundamental source of global food security, the growth and sustainability of the industry is continuously challenged by infectious diseases. The importance of protecting the poultry industry led to the establishment of biosecurity as the best measure available to avoid devastating economic losses from farms and threats to food safety. The poultry biosecurity principles are illustrated with application at the external (external biosecurity – location, visitors control and quarantine) and internal (internal biosecurity – cleaning and disinfection, litter/processing, procedures for handling feed) levels as well as vaccination programs. At the holding level, biosecurity has a positive impact on poultry health and is associated with a decline of important diseases like Newcastle disease, avian influenza and salmonella, lower mortality rates, and improved immunity which in turn results in the reduction of the use of antimicrobials. Biosecurity speaks to the possibility of improved growth performance, improved feed conversion ratio, and egg quality at the production level leading to economic profitability competences through reduced cost and enhanced productivity. This could access innovative solutions through the new technologies (sensors, artificial intelligence or automatic monitoring), but not all the problems related to the financial and knowledge gap in developing countries. However, future research should focus on biosecurity measures that are attentively tailored to suit local context, and integrated with the One Health approach, so as to enhance resilience of poultry systems in the long term.